Regulation of vascular remodeling by angiotensin-(1-9) - Chiong, Mario (2022)
The renin angiotensin system (RAS) is involved in the regulation of vascular remodeling induced by hypertension, vascular injury and inflammation. Angiotensin II (Ang II) is the most important peptide of the classical RAS pathway. Ang II exerts its biological action by binding to AT1 (AT1R) and AT2 (AT2R) receptors. The discovery of the homologous angiotensin I converting enzyme (ACE2), unmasked an intricated system of RAS regulation. In the counter-regulatory RAS pathway, Ang-(1-7) binds and activates Mas receptor (MasR), while Ang-(1-9) binds and activates AT2R. This review is focused in the inhibitory effects on vascular remodeling of ACE2, Ang-(1-9) and AT2R. Because of these vascular effects, the manipulation of the counter regulatory RAS emerges as a suitable therapeutical alternative to treat vascular diseases.